AN Audit Evidence: Mampukah Menghadapi Fraud? - Uty Wury Ayu Vitriany; Lilis Ardini (Universitas Katolik Darma Cendika, 2024)
Finding out whether auditors can uncover fraud in a business using audit evidence is the goal of this study. In order to back up their findings and suggestions on an entity's financial accounts, auditors gather what is known as audit evidence. Investigating whether fraud in financial reports or other types of fraud may be aided by properly using audit data is the goal of this study. The significance of audit evidence in bolstering attempts to detect and manage fraud is further illuminated by this study. An auditor's ability to identify and prevent fraud that can hurt the business depends on his or her familiarity with the function and proper application of audit evidence. Furthermore, this study lays a solid groundwork for future improvements to audit methodologies and processes that can tackle the ever-increasing complexity of fraud. A literature review, which comprises gathering and evaluating information from several relevant sources, is the research methodology used. Because it can check the accuracy and fairness of information, uncover suspicious patterns and anomalies, disclose the truth about company transactions and activities, and give appropriate proof, audit evidence plays a significant role in detecting fraud, according to the study findings. Auditing evidence must be collected in an impartial, independent, and truthful manner if auditors are to be successful in detecting fraud. The significance of audit evidence in bolstering attempts to detect and manage fraud is further illuminated by this study.